1977
DOI: 10.1161/01.res.41.6.830
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the pressure- and the volume-hypertrophied rat heart.

Abstract: We studied hearts in which hypertrophy was caused by both pressure and volume overload. Pressure hypertrophy was induced by an aortic constriction; volume hypertrophy was induced by an iron-copper deficiency (anemia). The ventricular weight was increased by 34% in the pressure-hypertrophied hearts at the end of 6 weeks. The ventricular weight was increased by 54% in the volume-hypertrophied hearts at the end of 3 months. A potassium arrest-formalin fixation technique was used to produce a "diastole-like" ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
2

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 19 publications
2
5
2
Order By: Relevance
“…However, our work is in contrast to the results of Lin et al (1977) who have shown in the rat that apparently there are no regional dimensional differences 3 months after volume overloading by anemia. However, species differences, and the gradual onset of volume overload in this preparation, may account for this disparity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our work is in contrast to the results of Lin et al (1977) who have shown in the rat that apparently there are no regional dimensional differences 3 months after volume overloading by anemia. However, species differences, and the gradual onset of volume overload in this preparation, may account for this disparity.…”
Section: Discussioncontrasting
confidence: 99%
“…Fischl (1977) and Vokonas (1973) examined ventricular shape angiographically in patients with chronic aortic and mitral regurgitation and showed that eccentricity decreased compared to a control population, also suggesting a more globular heart with volume-overload lesions. In contrast, however, Lin et al (1977) demonstrated conflicting data in the volume-overloaded rat heart model produced by 3 months of a low iron diet resulting in significant anemia. They found essentially no difference in the ratio of the minor to major axis in volume-overloaded hearts compared to controls.…”
Section: Early Changes In Left Ventricular Regional Dimensions and Fumentioning
confidence: 99%
“…The theoretical association between pressure overload and concentric hypertrophy (17,18,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), with increased myocyte cross-sectional area as the predominant feature, has been supported by experimental data (19,33). In agreement with the aforementioned findings, the change in myocyte volume resulting from the left ventricular pressure overload induced in the present study was primarily due to increased cross-sectional area.…”
Section: Discussionsupporting
confidence: 89%
“…Though initially compensatory, this process may exhaust itself and consequently transition to a maladaptive course. magnetic resonance imaging; finite element modeling THE DISCRETE, PHYSIOLOGICAL states of hypertrophic remodeling (19,30) and congestive heart failure (13) have been well studied. The dynamic nature of the heart allows it the plasticity to progressively change structurally to accommodate an inciting stimulus in an attempt to maintain parameters, such as myocardial mass and cardiac output, within physiological ranges (3).…”
mentioning
confidence: 99%